Women Directors and Firm Profitability: The Role of Corporate Environmental Responsibility Engagement - Atika Fairuzi; Bambang Tjahjadi (Jurnal Akuntansi dan Keuangan, 2022)
Women in the professional world are still experiencing inequality, discrimination, and obstacles in achieving top management positions. The role of women in improving the company's financial performance is still being debated to this day. This study aims to investigate the role of women directors in 129 manufacturing companies in Indonesia from 2015 to 2019. The data obtained were analyzed using structural equation modelling – partial least square (SEM-PLS). This study found that corporate environmental responsibility engagement did not mediate the relationship between women directors and firm profitability. This study found a significant negative relationship between women directors and corporate environmental responsibility but a significant positive influence between corporate environmental responsibility engagement and firm profitability. However, this study found no significant relationship between women directors and profitability.